Demonstration of a flexible electro-optic polymer modulator with a low half-wave voltage for ECG signals acquisition. (September 2022) - Li, Hongqiang; Lin, Zhilin; Wang, Yingjie; An, Zhixuan; Zhang, Shanshan; Zhang, Zanyun; Tang, Chunxiao; Li, Enbang; Prades Garcia, Juan Daniel
Highlights: A flexible full-polymer M-Z EO modulator with a low half-wave voltage is proposed. The results show that the modulator has the ability to detect human ECG signals. The low half-wave voltage was measured to be 2 V and the loss of the device was −2.1 dB. Abstract: Polymer-based electro-optic (EO) modulators have the advantages of low half-wave voltages and a low-cost preparation process and thus have extensive application prospects. A flexible, low half-wave voltage SU-8 Mach–Zehnder (M-Z) EO polymer modulator was proposed for human electrocardiogram (ECG) signal detection; polydimethylsiloxane (PDMS) was used as the substrate, and crosslinked polymer disperse red 1 (DR1)/SU-8 was used as the waveguide core layer. PDMS surface modification and SU-8 polarization were achieved, and the device was prepared by spin coating, ultraviolet (UV) lithography, wet etching and low-temperature sputtering. The experimental results show that the modulator initially operates in a linear operating regime under unbiased voltage conditions, and direct linear modulation of the voltage can be realized. After the preparation process, the low half-wave voltage was measured to be 2 V with a core size of 4000 μ m ×22000 μ m, and the loss of the device was −2.1 dB.